2019
DOI: 10.1039/c8dt04938f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning a robust system: N,O zinc guanidine catalysts for the ROP of lactide

Abstract: Four non-toxic, highly active and robust complexes have been used in the ring opening polymerisation of non-purifed lactide to substitute Sn(Oct)2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 61 publications
0
47
1
3
Order By: Relevance
“…A long known active and robust catalyst family for the ROP of LA are guanidine complexes, which have relevant properties for industrial use [12c,e, 21, 25] . In the last few years, very active N , O ‐donor zinc guanidine complexes have been reported [12d, 22] . However, the activity was slightly less compared to Sn(Oct) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A long known active and robust catalyst family for the ROP of LA are guanidine complexes, which have relevant properties for industrial use [12c,e, 21, 25] . In the last few years, very active N , O ‐donor zinc guanidine complexes have been reported [12d, 22] . However, the activity was slightly less compared to Sn(Oct) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…By polymerization experiments at different catalyst concentrations (up to 2000 : 1 per zinc), it was possible to obtain the rate constant k p from the linear fit by plotting the different k app values against the catalyst concentration. Compared with the k p from the recently published zinc guanidine catalyst [ZnCl 2 (TMG5NMe 2 asme)] with a value of 6.10±0.34×10 −2 L mol −1 s −1 complex 2 with k p =8.59±0.36×10 −2 L mol −1 s −1 is slightly faster. In a comparison to the active zinc catalyst Zn(CH 3 COO) 2 with a conversion of 69 % after 24 h ([M]/[I]=500 : 1) the herein presented systems with a conversion of 79 % after 41 min ([M]/[I]=500 : 1) are significantly faster …”
Section: Resultsmentioning
confidence: 81%
“…Despite an anionic ligand system, the complexes show a high degree of tolerance to the impurities in the monomer and produce industrially useful PLA with molar masses of up to 71 000 g mol −1 and a conversion of 78 %. With a k p =8.59±0.36×10 −2 L mol −1 s −1 , the systems are slightly faster than the recently published zinc guanidine complex and show that this class of ligands in combination with zinc also has a high potential to replace the currently industrially used catalyst Sn(Oct) 2 . Mechanistic investigations have shown that the dinuclear complex is present in melt of lactide as a mononuclear unit.…”
Section: Discussionmentioning
confidence: 80%
“…Folglich ist Komplex 1 fast dreimal so schnell wie der bisher schnellste, robuste Katalysator für die ROP von LA unter industriellen Bedingungen: ein Eisen‐Guanidin‐Komplex mit einem k p ‐Wert von 0.554±0.02 L mol −1 s −1 [14c] . Ein Vergleich von Komplex 1 mit dem industriell verwendeten Sn(Oct) 2 ergibt eine um fast eine Größenordnung erhöhte Geschwindigkeitskonstante ( k p =0.167 L mol −1 s −1 ) [12d] . Die resultierenden farblosen und transparenten Polymere haben hohe Molmassen von bis zu 100 000 g mol −1 , also typische Molmassen für verschiedene Anwendungen etwa Verpackungen oder im medizinischen Bereich [11b] …”
Section: Ergebnisse Und Diskussionunclassified
“…Eine seit langem bekannte aktive und robuste Katalysatorfamilie für die ROP von LA sind Guanidinkomplexe, die für den industriellen Einsatz relevante Eigenschaften aufweisen [12c,e, 21, 25] . In den letzten Jahren wurde über sehr aktive N,O ‐Donor Zink‐Guanidin‐Komplexe berichtet [12d, 22] . Allerdings war die Aktivität im Vergleich zu Sn(Oct) 2 etwas geringer.…”
Section: Introductionunclassified